Formulation Functional Powder Drink Of Avocado (Persea americana Mill.) Seed And Star Anise (Illicum verum Hook.f.) - Rini Tri Hastuti; Arum Dwi Agustin; Dewi Wulan Dari (Poltekkes Kemenkes Surakarta, 2022)
Background: Production of avocados in Central Java has increased every year, and products from seeds that have not been utilized optimally will be produced. Processing avocado seeds is very necessary so that they become foods that have a high selling value while maintaining the content of antioxidant compounds contained therein. One way to optimize is to make avocado seed powder that can be processed into a functional powder drink. Methods: The method and the type of research conducted quantitatively using a descriptive design. Parameter tests include quality tests, flavonoid qualitative tests with color reaction tests, flavonoid quantitative tests, and antioxidant activity tests using a UV-Vis spectrophotometer. Results: Quality tests show that the functional powder drink has a smooth texture, a whitish brown color, a distinctive smell, and a sweet taste. The pH was 6,599±0,038, 6,699±0,017, and 6,741±0,030. A qualitative test of flavonoids shows positive results, followed by a quantitative test of flavonoids obtained flavonoid levels of 12,044±0,009428%, 12,214±0,009428%, and 12,419±0,009428%. Antioxidant test results for functional drinks showed an IC50 value of 128,422 ± 0.0094 mg/L categorized as a moderate level of antioxidants. Conclusion: The organoleptic test of functional powder drinks of avocado (Persea americana Mill.) seed and star anise (Illicum verum Hook f.) revealed a whitish chocolate color, typical spice smell, typical spice and sweet taste, and a fine powder texture.